Modified Lipschitz Optimization and its Application to Maximum Power Point Tracking Control for Photovoltaic Systems. Issue 6 (2nd March 2022) - Masuda, Eiji; Wakasa, Yuji; Adachi, Ryosuke
Abstract: In this paper, we propose a modified Lipschitz optimization (LO) method and apply it to maximum power point tracking (MPPT) control for photovoltaic (PV) systems. The standard LO can find a global maximum of a Lipschitz continuous function over a closed interval in a deterministic way. However, the standard LO tends to evaluate low objective function values, and this feature leads to low MPPT efficiency in its application to MPPT control. The proposed method skips the evaluation of low objective function values (i.e., low power points) by using prior information on the output characteristics of a PV array. Moreover, we show theoretically that the proposed method guarantees convergence to a global optimal solution. We compare the proposed method with some of well‐known MPPT methods and verify its effectiveness through simulations. © 2022 Institute of Electrical Engineers of Japan. Published by Wiley Periodicals LLC.